Perception of a Classical Poetic Text by Fan Fiction Readers (Филологический класс, 2020)
The article is devoted to the study of the relationship between fan fiction as a type of secondary text and a classical text, which reveals the regular patterns of transformation of the structures of an artistic text in mass consciousness. In this aspect, the connection of the secondary text with a specific source – the classical text – is particularly important in relation to the problem of reading strategies and understanding of the literary text, especially a poetic one. The purpose of this article is to show how a classical text changes when it is transformed into a fan-fiction one. The study employs the methods of research of artistic adaptations and a comprehensive analysis of the literary text. The functioning of the secondary text presupposes active interaction between the reader and the artistic structure. This interaction is more often expressed in the form of repetition or “retelling” which changes the meanings of the original text to meet the tastes and expectations of the reader. In this situation, the co-creation of the author and the reader is not only expressed via intensive but also extensive development of the author’s artistic universe by the reader. The analysis of fan fiction texts based on the poem by A. Akhmatova “The Grey-Eyed King” has revealed that the borrowings, references and alterations of the classical work relate to two artistic structures of the text – the main character and the plot (the linguistic level does not become an object of readers’ perception). In the first case, it is a plastic adaptation of a character recognized by the reader and provision of details to the descriptions; in the second – it is a game with the events: their sequence, content, and interpretation. The text of the ballad is transformed into a fantasy story with an adventure plot and a tragic finale. It is the event-based level of the text, the genre formula and the romanticized main character that become the key points linking fan-fiction with the source, and it is they that become the main objects of rethinking in the reader’s creative work. Yet the novelty of rethinking is illusionary: the text should be familiar and wellknown, therefore the main character is placed in a familiar and understandable environment and the plot is filled with characters familiar to the reader. Such interpretations of the poem by Akhmatova are likely to appear due to the reader’s former experience dominated by works of mass culture.